Wales Inverse Care Law Programme - Design and Implementation of Routine Data Evaluation and Lessons Learned - Ashley Akbari; Rowena Griffiths; Alice Puchades; Sara Thomas (International Journal of Population Data Science, 2020)
Introduction The Inverse Care Law (ICL) programme in Wales was setup to tackle health inequalities. Eligible populations from deprived communities, at higher risk of cardiovascular disease (CVD) were invited to a health-check and offered appropriate lifestyle and clinical interventions.